Familial micropenis associated with bilateral cryptorchidism: A case report - Jeannot Baanitse Munihire; Justin Nzanzu Matungulu; Faustin Tatana Museketwa; Joshua Muhumuza (Elsevier, 2023)
Introduction: Micropenis refers to a penile length smaller than 2.5 standard deviations below the mean. Undescended testicle, also known as cryptorchidism, is a frequent reason for young males to be referred for urologic evaluation. Unilateral Cryptorchidism is a common condition in the pediatric population but bilateral cryptorchidism are rare and most uncommonly associated with micropenis. Case presentation: We present two cases of the 4 days and 28 months old males born of the same mother with micropenis and bilateral cryptorchidism but no family history of these anomalies.Both the neonate and the big brother had an empty scrotal sac and a penis 1.1 cm and of 0.9 mm length respectively on physical examination. No other abnormalities were diagnosed. Sonography, hormonal therapy and orchidopexy were successfully done for the older sibling. Patients with cryptorchidism have a relative risk of testicular cancer that is approximately five times higher. The condition known as cryptorchidism is linked to 10% of all testicular cancers. Conclusion: Our findings suggest that micropenis and cryptorchidism can co-exist and have a familial pattern. Any child who presents with either should have a though examination to rule out the other. Also when one child presents with both anomalies, clinical evaluation of the older siblings may be necessary to rule out a similar condition more so in resource limited settings where some babies are born out of hospitals with no initial physical examination after birth.